Investigation on propagation characteristics and performances of RDE fueled by kerosene under low oxygen mass fraction. (15th March 2023) - Zhou, Jianping; Song, Feilong; Wu, Yun; Cheng, Peng; Xu, Shida; Yang, Xingkui; Li, Yinghong
Highlights: Propagation characteristics of detonation waves and performances under low oxygen mass fraction are analyzed. Relationships between total pressure gain and combustion efficiency are summarized. Effects of inlet pressure ratio and heat capacity intensity of combustor on total pressure gain are investigated. Abstract: The application of rotating detonation chambers instead of traditional afterburners is expected to improve the overall performance of turbine engines. Based on the background, the effects of oxygen mass fractions, inlet temperatures, equivalent ratios and nozzle outlet areas on the propagation characteristics and performances of RDE under low oxygen mass fractions and lean fuel conditions are investigated. It is observed that increasing the inlet temperature can widen the lower boundary of the oxygen mass fraction maintaining the propagation of RDWs, but decrease the propagation stability of the detonation waves. Although increasing the equivalent ratio has little effect on the lower boundary of the oxygen mass fraction, the propagation stability of the detonation wave is enhanced. It is found that reducing the nozzle outlet area ratio can effectively broaden the lower boundary of the oxygen mass fraction. With the decrease of oxygen mass fraction, the total pressure gain and combustion efficiency show a decreasing trend. Reducing the inlet air temperature, increasing equivalent ratios and reducing the nozzle outlet area ratio are conducive to reducing the inlet pressure ratio, which in turn reduces the inlet air loss and improves the total pressure gain. Combustion efficiency is higher under conditions of high oxygen mass fractions, low inlet temperatures, low equivalent ratios and small outlet area ratios.